Histopathologic Evaluation of Endometrium in Patients with Ectopic Pregnancy - Dilbaz, Serdar; Özdeğirmenci, Özlem; Dilbaz, Berna; Taşçı, Yasemin; Güvendağ Güven, Emine Seda; Haberal, Ali; Özfuttu, Ahmet (Gynecology Obstetrics & Reproductive Medicine, 2006)
OBJECTIVE: To evaluate the endometrial changes in patients with proven ectopic pregnancies and the v alue of endometrial histopathology in diagnosis of ectopic pregnancies. STUDY DESIGN: Medical records of 71 patients with prov en ectopic pregnancies and who had endometrial curettage results were rev iewed. Ectopic pregnancy was conf irmed either at operation or at transv aginal ultrasound ev aluation with clearly visualized characteristic adnexal mass in the presence of an empty uterus and serum beta-subunit human chorionic gonadotropin level abov e the discriminatory zone. Histopathologic f indings of the endometrial curettage materials were ev aluated. RESULTS: The mean age of the patients was 30±5.9 y ears. The mean gestational age (by date of last menstrual period) at presentation was 36.9 day s. The most common symptoms at presentation were both v aginal bleeding and missed menstruation. Rev iew of the endometrial curettages revealed that the most common type of endometrium associated with ectopic pregnancy was secretory (52.2%) followed by decidual reaction (15.5%), proliferative endometrium (14.1%), Arias-Stella reaction (11.2%), and endometrial f ragments (7%). CONCLUSION: Since ectopic pregnancy is associated with v arious ty pes of endometrial histopathology, it is not valuable in the diagnosis and should be performed in selected patients f or differential diagnosis when TVUS, serial serum b-HCG levels are inconclusive.